An examination of factors affecting healthy building: An empirical study in east China. (20th September 2017) - Mao, Peng; Qi, Jiao; Tan, Yongtao; Li, Jie
Abstract: With economic development, there is an increasing demand for healthy working and living environments. Health issues of buildings have become increasingly important because people spend most of their time in buildings. One of their major concerns is whether the building is healthy or not. Many research efforts have been made regarding building health from various perspectives, such as eco-building, sustainable building, low-carbon building and green building. However, these studies cannot represent the health status of building comprehensively and appropriately. Based on comprehensive literature review, the connotation of healthy building was defined and 30 impact factors that affect healthy buildings were identified by bibliometric analysis and expert interview. A questionnaire survey was conducted to identify the importance of these key factors. Sixteen factors were identified as key impact factors (KIFs) with the importance index above 80. Furthermore, these 30 factors were classified into three principal components by using principal component analysis (PCA). At last, a framework integrating all these impact factors of a healthy building during its life cycle was developed, which provides a thorough picture of the impact factors and their classifications. The findings in this study can also help people gain deep understandings of healthy building, provide theoretical support for the design, construction and operation of healthy building, and promote the development of healthy building.